Princess - Sasson, Jean P. (London Bantam Books, 1997)
The story of a Saudi Arabian princess, hidden behind the veil with no vote, no freedom, no control over her own life. Princess exposes life within the 2000 strong Saudi Arabian royal family.
English Fiction.
Keywords: Sultana -- Saudi Arabia -- Women--Social conditions